Kinematic measurement of 12-week head control correlates with 12-month neurodevelopment in preterm infants. Issue 2 (February 2015) - Bentzley, Jessica P.; Coker-Bolt, Patty; Moreau, Noelle G.; Hope, Kathryn; Ramakrishnan, Viswanathan; Brown, Truman; Mulvihill, Denise; Jenkins, Dorothea
Abstract Background Although new interventions treating neonatal brain injury show great promise, our current ability to predict clinical functional outcomes is poor. Quantitative biomarkers of long-term neurodevelopmental outcome are critically needed to gauge treatment efficacy. Kinematic measures derived from commonly used developmental tasks may serve as early objective markers of future motor outcomes. Aim To develop reliable kinematic markers of head control at 12 week corrected gestational age (CGA) from two motor tasks: head lifting in prone and pull-to-sit. Study design and subjects Prospective observational study of 22 preterm infants born between 24 and 34 weeks of gestation. Outcome measures Bayley Scales of Infant Development III (Bayley) motor scores. Results Intrarater and interrater reliability of prone head lift angles and pull-to-sit head angles were excellent. Prone head lift angles at 12 week CGA correlated with white matter NAA/Cho, concurrent Test of Infant Motor Performance (TIMP) scores, and 12-month Bayley motor scores. Head angles during pull-to-sit at 12-week CGA correlated with TIMP scores. Conclusions Poor ability to lift the head in prone and an inability to align the head with the trunk during the pull-to-sit task were associated with poorer future motor outcome scores. Kinematic measurements of head control in early infancy may serve as reliable objective quantitative markers of future motor impairment and neurodevelopmental outcome.